4 x 2 )- 2 3 3x 1 )= 5 2x
![4 x 2 )- 2 3 3x 1 )= 5 2x](https://d1avenlh0i1xmr.cloudfront.net/db81f035-09f8-45be-886d-476e2e153d2d/slide24.jpg)
- Solve 2x 1 3 3x 2 4 2 x 5
- 3 4 1 2 x 8 )=- 2 5 2x 5 )+ 3x
- 3x 1 2 4x 2 4 2x 4 3 x 5 6
- 1 /( x 2 3x 3 )+ 2x 2 3x 4 )= 6 /( x 2 3x 5
- 5x 2 )( x 1 )- 3x x 2 x 3 )- 2x x 5 )( x 4
- 2x 2 20x 50 3x 3 x 2 1 4 x 5 3
- 3x 2 7 4 x 1 )/ 5 2 3 2x 1
- 3 5 2x 1 6 )- 4 3 3x 2 4 )- 1 5 x 2 3 )+ 1 5 0
- 3 x 2 )- 5 2x 1 )- 2 3x 4 )+ 10 0
- 3 x 2 )- 5 2x 1 )- 2 3x 4 )- 4 0
- 3 x 2 )- 5 2x 1 )+ 2 3x 4 )+ 10 =- x